Urban planning policies to the renewal of riverfront areas: The Lisbon metropolis case - Medeiros, E. (2021)
Urban planning offers various design possibilities to solve fundamental challenges faced in urban areas. These include the need to physically renew old industrial and harbour riverside areas into liveable, inclusive and sustainable living spaces. This paper investigates the way urban planning policies have helped to renew the waterfront areas in the Lisbon metropolis in the past decades. For this purpose, the contribution of the European Union (EU) and national urban development plans over the past decades are analysed. The results demonstrate an intense renewal of the waterfront areas in the Lisbon metropolitan area (LMA), particularly in Lisbon over the past three decades into leisure, ecologic and touristic areas, vis-à-vis the previous industrial and harbour vocation